Praktik Arisan Menurun di Kelurahan Cabbenge Kecamatan Lilirilau Kabupaten Soppeng: Tinjauan Mazhab al-Syafi’i dan Mazhab Hambali - Nur Aisyah; Wijaya, Abdi; Amir, Rahma (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2023)
The main problem in this study is how the views of the Shafi'i and Hambali Schools on the practice of social gathering decreased in Cabbenge Village, Lilirilau District, Soppeng Regency The type of research used in this study is field research which is descriptive analytic. The sources of this research are the organizers of the social gathering and people who have joined the social gathering group. Furthermore, the data collection methods carried out are observation, interviews, and documentation. Then, data processing techniques and data analysis are carried out through data reduction, data presentation, and conclusion or verification. In this study, it can be concluded that this declining arisan practice has a debt contract that has different advantages and disadvantages for each participant. The existence of these advantages and disadvantages. The distinct advantage is that the initial participant gets a time gain and a loss in the amount of money earned. Whereas, the end participant gains the amount of money earned and the time loss. So that social gathering is not allowed because it contains elements of usury'. The implication of this research is for parties who carry out arisan with a declining system in order to be able to carry out the arisan activities in accordance with the basics of Islamic law that have been regulated in the Quran, as-Sunnah, Ijma, along with the provisions of the scholars, and in the implementation of declining arisan there should be no difference (+/-) between what is paid and obtained by each member in order to create the main purpose of the arisan, namely help.